Estudo da aplicação dos conceitos análise ativa e tempo-ritmo no treinamento do Grupo Fisções EBA/UFMG (2002-2010) - Frederico Ramos Oliveira (2011)
The research described here investigated the work of the Group Fiscoes (2002-2010), describing and analyzing the relationship between theory and practice of Active and Analysis of Time-Rhythm theater based on Stanislavski. Initially, a literature review was developed in order to establish a theoretical framework of the content addressed. Secondly, it describes the practical work of the Group, with its laboratories-Time Pace Theatrical and Psychophysical training, offering workshops and assembly of the show New York City Marathon. Following, we analyze the application of theoretical concepts in practical work of Fiscoes. In conclusion, we have an understanding of the Stanislavski system extended through the deepening of its other content, such as the super, reinforcing the idea that each technical element is enhancedintegration with others.